Pendapatan Usaha Mikro Kecil dan Menengah (UMKM) di Era Bisnis Digital - Khusnul Hasiah; Askari Zakariah; Novita Novita (Journal of Islamic Economics and Finance, 2024)
Based on a statement from the Indonesian E-Commerce Association, the number of MSME members in various markets increased by 3.8 million people in 2020, from 1 million people to 4.8 million people in March 2021. This increase is in line with survey results which show a significant increase significant number of MSMEs in Indonesia in the first quarter of 2020, when the COVID-19 pandemic began. This type of research writing is a type of library research which uses 30 references from 50 journals, where the library sources are taken from Google Scholar. Regarding the approach to this research, it is a qualitative approach and domain data analysis, namely a method of collecting data by understanding and studying theories from various literature related to this research. SME income has decreased in the COVID-19 era, so e-commerce has a positive impact on MSME income. Because e-commerce can expand the reach of the SME market and be able to reach more consumers. Apart from that, e-commerce can also reduce operational and marketing costs, thereby increasing MSME profits.